Metaarchaeology
VII, 343 p.
Keywords: An idea of the philosophy of archaeology can best be gained by showing what it is, what the issues are, who is working in the field, and how they proceed. Reading Lester Embree's Metaarchaeology provides the best possible introduction to the field, since in it several leading archaeologists show how accessible and interesting the current archeological literature is, and currently active philosophers of archaeology reveal something of the current state of discussion on the subject. Bibliographies have also been developed of the philosophy of archaeology as well as of selected parts of the component that can be called metaarchaeology. Finally, an historical introduction has been included to show the variety of metascientific as well as orientational standpoints that philosophers of archaeology have had recourse to for over two decades, followed by speculation about the future of the discipline within the philosophy of science.